Comprehensive circular RNA expression profile of lung adenocarcinoma with bone metastasis: Identification of potential biomarkers - Cai, Ying; Zhu, Chunlan; Wang, Yanfei; Jiang, Yiqian; Zhu, Zhongxin (Frontiers in Genetics, 2022)
Background: Lung adenocarcinoma (LUAD) has a significant tendency to metastasize to the bone, with severe comorbidities. Recent studies have reported that circular RNAs (circRNAs) are involved in various cancer metastasis-related physiological cellular processes. However, their role in LUAD with bone metastasis (LUAD-BM) remains unknown. Methods: Bone metastasis (BM) circRNAs were identified using high-throughput sequencing and validated by quantitative reverse transcription-PCR (qRT-PCR). Bioinformatic analyses were used to predict the potential functions of the differentially expressed circRNAs. The effects of circ_0096442 on the growth and metastasis of A549 cells were detected in a co-culture system of A549 and bone marrow-derived cells. Results: There were 598 (238 upregulated and 360 downregulated) 390 (187 upregulated and 203 downregulated) and 644 (336 upregulated and 308 downregulated) differentially expressed circRNAs between LUAD-BM and LUAD, LUAD-BM and healthy individuals, and LUAD and healthy individuals, respectively. These differentially expressed circRNAs play important roles in cellular components, biological processes, and molecular functions. Moreover, they map several pathways related to BM, including DNA repair, DNA damage, and osteoclast differentiation. The results validated by qRT-PCR for the five most dysregulated circRNAs are consistent with the sequencing data. Additionally, circ_0096442 was found to promote the growth and metastasis of LUAD in a bone microenvironment. Conclusion: Our findings provide a novel and important circRNA expression profile of LUAD-BM and suggest that circ_0096442 may be a biomarker for LUAD-BM.